The Path Analysis of Ownership Structure and Dividend Payout Ratio on Firm Performance of Listed Companies in the Stock Exchange of Thailand - Bunnun, Wiwatwong; Chancharat, Nongnit (Journal of Business, Innovation and Sustainability (JBIS), 2022)
The objective of this study was to study the impact of ownership structure and dividend payout ratio on firm performance from 185 listed companies in the Stock Exchange of Thailand (SET) which was conducted from 2015 to 2019. The data were analyzed using path analysis to examine the effect between variables and the consistency of the model and empirical evidence. The result found that concentration ownership and institution ownership directly affected the dividend payout ratio. The dividend payout ratio also had a direct effect on firm performance. Moreover, the results of empirical evidence revealed that concentration ownership and institution ownership had an indirect effect on firm performance through dividend payout ratio which the model and empirical evidence were concordant in Thailand context, which was considered from the index value of concordance consisting of χ2 /df = 1.938, CFI = 0.998, GFI = 0.999, NFI = 0.997, RMSEA = 0.032, and RMR = 0.013.